THE EFFECT OF AN RME APPROACH USING THE TRADITIONAL CONGKLAK GAME TO IMPROVE MATHEMATICAL LITERACY AMONG ELEMENTARY SCHOOL STUDENTS - Maya Rahmayanti; Tarpan Suparman; Andes Safarandes Asmara (Prima: Jurnal Pendidikan Matematika, 2026)
Mathematics teaching at the primary level remains predominantly focused on procedural mastery. Consequently, many learners encounter challenges when required to use multiplication in authentic daily contexts. This study sought to investigate the impact of implementing the Realistic Mathematics Education model assisted by congklak on third-grade students’ multiplication literacy.  A quantitative method with a quasi-experimental pretest–posttest control group design was employed. The participants were 60 students in grade 3 at SDN Kondangjaya 3 for the 2025/2026 school year. The treatment group was Class III E, and the comparison group was Class III A. A validated and reliable 20-question multiple-choice test of mathematical literacy was used for data collection. Data were processed using descriptive analysis, paired-sample t-test, independent-sample t-test, and N-gain analysis. The findings indicated that the mean score of the experimental group increased from 58.46 to 81.85 following the treatment. Meanwhile, the control group’s mean only grew from 57.92 to 62.40. The independent samples t-test indicated a statistically significant difference between groups with p < 0.05. The N-gain score for the experimental group was 0.57, reflecting moderate effectiveness, while the control group obtained 0.09, reflecting low effectiveness. Overall, the results show that merging Realistic Mathematics Education with the cultural game congklak creates a contextual and meaningful learning process that effectively boosts students’ mathematical literacy. This instructional approach can be proposed as a creative alternative for teachers to implement contextual mathematics in elementary schools.